2002
DOI: 10.1083/jcb.200202114
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular signaling hierarchy determines direction of migration in opposing chemotactic gradients

Abstract: Neutrophils must follow both endogenous and bacterial chemoattractant signals out of the vasculature and through the interstitium to arrive at a site of infection. By necessity, in the setting of multiple chemoattractants, the neutrophils must prioritize, favoring end target chemoattractants (e.g., fMLP and C5a) emanating from the site of infection over intermediary endogenous chemoattractants (e.g., IL-8 and LTB4) encountered en route to sites of infection. In this study, we propose a hierarchical model of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
447
5
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(488 citation statements)
references
References 37 publications
31
447
5
2
Order By: Relevance
“…Interestingly, inhibition of p38 MAP kinase converted the inhibitory effect of 5-oxo-ETE on migration towards PGD 2 to enhancement, and this coincided with 5-oxo-ETE-induced p38 MAP kinase phosphorylation, which suggests that it is the MAP kinase pathway that determines the hierarchy of eosinophil chemoattractants. p38 MAP kinase has been shown to be essential for neutrophil orientation in opposing gradients of chemoattractants [36]. However, in contrast to the observations of Heit et al [36], where inhibition of p38 MAP kinase induced the activation PI-3 kinase and by that enhanced the chemotactic responsiveness of neutrophils, here we observed that p38 MAP kinase and PI-3 kinase acted in a consecutive manner in eosinophils.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, inhibition of p38 MAP kinase converted the inhibitory effect of 5-oxo-ETE on migration towards PGD 2 to enhancement, and this coincided with 5-oxo-ETE-induced p38 MAP kinase phosphorylation, which suggests that it is the MAP kinase pathway that determines the hierarchy of eosinophil chemoattractants. p38 MAP kinase has been shown to be essential for neutrophil orientation in opposing gradients of chemoattractants [36]. However, in contrast to the observations of Heit et al [36], where inhibition of p38 MAP kinase induced the activation PI-3 kinase and by that enhanced the chemotactic responsiveness of neutrophils, here we observed that p38 MAP kinase and PI-3 kinase acted in a consecutive manner in eosinophils.…”
Section: Discussioncontrasting
confidence: 99%
“…p38 MAP kinase has been shown to be essential for neutrophil orientation in opposing gradients of chemoattractants [36]. However, in contrast to the observations of Heit et al [36], where inhibition of p38 MAP kinase induced the activation PI-3 kinase and by that enhanced the chemotactic responsiveness of neutrophils, here we observed that p38 MAP kinase and PI-3 kinase acted in a consecutive manner in eosinophils. This notion was based on the fact that inhibition of PI-3 kinase reversed the inhibitory effect of 5-oxo-ETE on eosinophil migration to enhancement, as did inhibition of p38 MAP kinase.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, several reports have shown that SAPK2/p38 is involved in chemokine-induced chemotaxis of cells (16,34,70,71). Our study also presents evidence that SAPK2/p38 and SAPK1/JNK1, but not ERKs, intervene in the control of MCP-1-induced MonoMac6 migration.…”
Section: Discussionsupporting
confidence: 75%
“…Chemoattractant control of neutrophil migration is complex, not least because the effect on chemotaxis may depend on agonist concentration and context, but also the in vivo milieu is a dynamic environment comprising multiple chemokine signals. There is intracellular signalling hierarchy, with end-target chemoattractants signalling predominantly through p38 MAPK [4]. Neutrophils are avid phagocytes, which recognise and rapidly ingest bacteria.…”
Section: Principal Effector Functions Of Neutrophilsmentioning
confidence: 99%